Homocentric sphere model: a novel network architecture supporting 6G dense deployment and high-speed mobility scenarios - LI Guoqing; WANG Peibo; CHEN Li; HU Bo; CHEN Shanzhi (Dianxin kexue)
5G ultra-dense network (UDN) was introduced to improve throughput, especially for static and low-speed scenarios, and thus cannot meet the demands that require high throughput and high mobile speed at the same time. For the new 6G scenarios that need to support both high-capacity and high-speed mobility in the future, a homocentric sphere model (HSM) network architecture was proposed, which adopted the control-plane/user-plane data separation and multiple transmission and reception point (TRP) cooperative transmission method to deal with the problem in densely deployed networks. The HSM was an effective method to improve the network capacity and cope with high-speed mobility in dense deployment networks by adopting control-plane/user-plane data separation and multiple TRP co-transmission to deal with the problems of high Doppler frequency shift effect and frequent switching of TRP in the dense deployment networks. The results demonstrate that the proposed homocentric sphere model can effectively reduce the Doppler shift effect in the high-speed mobility scenario of a densely organized network, and can provide higher network traversal spectrum efficiency.